REVIEW OF FIQH MUAMALAH ON THE PRACTICE OF BUYING AND SELLING TAMBOURINE MUSICAL INSTRUMENTS ONLINE AT SUARA TUNGGAL BAHANA SHOP - Wardah, Audiya Khilya (Universitas Nurul Jadid, 2024)
This study seeks to ascertain the prevalence of online transactions for purchasing and selling tambourine musical instruments at Toko Suara Tunggal Bahana and the perspective of fiqh muamalah about such transactions. The present study employs a qualitative research methodology, explicitly adopting a descriptive qualitative approach. The primary sources of data for this study were interviews and documentation. The obtained data is subjected to analysis through interactive methodologies, and conclusions are derived through the application of inductive reasoning. The study's findings indicate that selling and purchasing tambourine musical instruments at the Suara Tunggal Bahana shop was conducted online. The buyer possessed comprehensive knowledge regarding the characteristics of the goods, and the seller offered the buyer the option to return any damaged or defective products. However, it is essential to note that this option was contingent upon the presence of unedited video evidence during the package opening process. The permissibility of online tambourine musical instrument sales at Toko Suara Tunggal Bahana is supported by fiqh Muamalah since it adheres to the principles of salam sale and istishna sale and purchase, hence granting the buyer the right to khiyar.